PENGARUH EDUKASI MANFAAT ASI COLOSTRUM MELALUI MEDIA POSTER TERHADAP PENGETAHUAN IBU POST PARTUM - Nelfa F Takahepis; Dewi A Sudijanto; Petronela Mamentu (PT. Hasba Edukasi Mandiri, 2026)
Breastfeeding is a natural process, but many new mothers find it one of the most amazing parts of motherhood. Through health education, mothers can understand the benefits of colostrum, such as strengthening the baby's immune system, improving digestion, and preventing infections. The purpose of this study was to determine the effect of Lactation Education through Leaflet Media on Colostrum Breastfeeding in Post Partum at Bhayangkara Gr. III Hospital Manado. This research is experimental with pre experimental research design and using the